FreeTest 2.0: uma evolução do método FreeTest para a melhoria no processo de teste de software em micro e pequenas empresas - Louzada, Jailton Alkimin (2017)
The Information Technology (I.T) market is growing. In the age of information, world economies have been investing more and more in the services market. Within this competitive scenario, software testing is an important component for raising the quality of software developed in Brazil and in the global competitiveness cenario. However, Small and medium-sized enterprises (SMEs) have limited resources for investments in software testing maturity processes, tools and models in their business. Faced with this, this work has as main proposal to produce an apparatus to improve the process of software testing for SMEs. Objective: As the main objectives, this study proposed a more update version of the FreeTest 1.0 process, as well as practical instructions on how to implement the activities suggested in the process, all this formatted in a new process and a wizard respectively. Methodology: In order to fulfill the objectives of this work, the FreeTest 2.0 process was created as an improvement of the FreeTest Method process, focused mainly on Agile techniques, DevOps and aligned with the SMEs ecosystem. And the FreeTest Wizard, which consists of a deployment guide that supports the implementation of the process in a didactic, dynamic and flexible way. Another contribution of this work was the creation of support tools to disseminate this knowledge and content management, in this case the creation of a web platform, distributed free of charge and in the format "as a Service". Finally, the results and conclusions can be seen in the final chapter of this work.